A Nerve Conduit Containing a Vascular Bundle and Implanted with Bone Marrow Stromal Cells and Decellularized Allogenic Nerve Matrix. Issue 2 (February 2017) - Kaizawa, Yukitoshi; Kakinoki, Ryosuke; Ikeguchi, Ryosuke; Ohta, Soichi; Noguchi, Takashi; Takeuchi, Hisataka; Oda, Hiroki; Yurie, Hirofumi; Matsuda, Shuichi
Cells, scaffolds, growth factors, and vascularity are essential for nerve regeneration. Previously, we reported that the insertion of a vascular bundle and the implantation of bone marrow-derived mesenchymal stem cells (BM-MSCs) into a nerve conduit promoted peripheral nerve regeneration. In this study, the efficacy of nerve conduits containing a vascular bundle, BM-MSCs, and thermally decellularized allogenic nerve matrix (DANM) was investigated using a rat sciatic nerve model with a 20-mm defect. Lewis rats were used as the sciatic nerve model and for the preparation of BM-MSCs, and Dark Agouti rats were used for the preparation of the DANM. The revascularization and the immunogenicity of the DANM were investigated histologically. The regeneration of nerves through nerve conduits containing vessels, BM-MSCs, and DANM (VBD group) was evaluated based on electrophysiological, morphometric, and reinnervated muscle weight measurements and compared with that of vessel-containing conduits that were implanted with BM-MSCs (VB group). The DANM that was implanted into vessel-containing tubes (VCTs) was revascularized by neovascular vessels that originated from the inserted vascular bundle 5–7 days after surgery. The number of CD8 + cells found in the DANM in the VCT was significantly smaller than that detected in the untreated allogenic nerve segment. The regenerated nerve in the VBD group was significantly superior to that in the VB group with regard to the amplitude of the compound muscle action potential detected in the pedal adductor muscle; the number, diameter, and myelin thickness of the myelinated axons; and the tibialis anterior muscle weight at 12 and 24 weeks. The additional implantation of the DANM into the BM-MSC-implanted VCT optimized the axonal regeneration through the conduit. Nerve conduits constructed with vascularity, cells, and scaffolds could be an effective strategy for the treatment of peripheral nerve injuries with significant segmental defects.